Research Of Lithium-Ion Batteries Anode Materials - Wang Shengzhi (MATEC Web of Conferences)
As the energy requirement constantly increases and paying attention to environmental protection day by day, the lithium-ion battery is a sort of efficient energy storage technique and is applied in many areas widely. However, it is of great importance to satisfy the demand for high- performance applications such as electric vehicles and increase the performance of lithium-ion batteries further, especially the performance of anode materials. The article first introduces the working mechanism of lithium-ion batteries. Later advantages and disadvantages of graphite, tin, and silicon are emphatically discussed as anode materials. Finally, regarding the above issues. Various modification strategies are proposed. For graphite, its electrochemical properties can be effectively improved by surface modification such as gas phase oxidation and physical coating. Using the structure design strategy of hollow carbon nanofiber and silicon composite, the silicon carbon anode material can obtain higher conductivity, and its cycle stability is also significantly improved. The modification of tin-carbon composite improves the electrochemical stability of tin-based material by optimizing the preparation process. These modification strategies greatly improve the properties of lithium-ion batteries. The paper reviews the properties, optimization methods, and obstacles of anode materials for lithium-ion batteries, with the intention of providing insights into further exploration and advancement in this field.